تأثير الفصول المدعمة بأنترنت الأشياء في تطوير مهارات تعلم اللغة الانجليزية كلغة أجنبية على طلاب التعليم العالي في ليبيا(دراسة تجريبية) - Al-Baoui, Fawzia Abuajila (Al-Qurtas, 2025)
Online teaching and learning is a new and evolving educational approach. Its implementation requires well-trained teachers and professional facilitators. The virtual teaching and learning process requires many advanced tools and reasonable costs for effective educational systems. The Internet of Things is a new approach in some countries, such as Libya. This modern means of teaching and learning requires complex and supported work across the educational chain, from the level of students to the level of the Libyan Ministry of Education, to achieve the system’s goal (i.e., education).The use of the Internet of Things serves and plays many roles, such as helping students with various disabilities, anxious students, students from diverse backgrounds, bored and lazy students, and learners with individual differences. The Internet of Things also assists teachers with limited experience in the teaching and learning process. IOT tools provide a comfortable environment for those who have the ability to send or receive information. In addition to, the success of the educational process with the Internet of Things is guaranteed, as it can serve a variety of purposes within the educational process. Furthermore, students of this age are mostly fond of using any type or application installed using technology and are willing to accept any information provided through these applications or any type of social media. Finally, this study consists of five sections. In the first section; there is a an introduction part, in which the causes of the study are ـ Part Eight September 2025 (3) Al qurtas Issue Twenty Seven mentioned, statement of the problem, the questions of the study, the hypothesis of the study, the goals of this study. In addition to, the value of the study. The second section reviews the literature and previous studies related to this study. The next section, reports the methodology, sample of the study and the instruments used for collecting and analyzing the data and also it includes the restrictions of the study. The fourth section gives discussions and results of this study. The last section summarizes the conclusion and the recommendations of this study.